Meningkatkan Motivasi Belajar Pakat Melalui Model PBL pada Peserta Didik SD Santa Ursula BSD - Yustina Dina Yunianti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to determine the improvement of learning motivation and affective outcomes in the dimensions of teamwork and critical thinking through the Problem-Based Learning (PBL) model among students at Santa Ursula BSD Elementary School. The research is based on the issues of low learning motivation, lack of student engagement in learning, and the need to enhance social skills within the context of Catholic Religious Education and Character Education. This study employs classroom action research, with steps including planning, implementation, observation, and reflection in each cycle. The research consists of two cycles conducted with third-grade students in Phase B at Santa Ursula BSD Elementary School, focusing on the subject "The Origins of Moses and His Works for His People" in Catholic Religious Education and Character Education. The research was carried out in September 2024.Data collection techniques included observation and learning motivation rubrics, as well as affective rubrics for the dimensions of teamwork and critical thinking. The data analysis used qualitative descriptive techniques. The results of the first cycle showed an increase in learning motivation and student engagement, although the expected target was not yet achieved. In the second cycle, there was a significant improvement in both learning motivation and students' affective outcomes. The research demonstrated a 36% increase in motivation and student engagement in learning Catholic Religious Education. It is hoped that the PBL approach will create a more active and collaborative learning environment, in line with the objectives of the Merdeka Curriculum and the values in the Pancasila Student Profile.